36th Annual Hawaii International Conference on System Sciences, 2003. Proceedings of The 2003
DOI: 10.1109/hicss.2003.1174254
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impacts of knowledge (re)use and organizational memory on the effectiveness of strategic decisions: a longitudinal case study

Abstract: Two forces that dramatically affect the sustainability of firms' competitive advantage in the new competitive landscape have been identified as globalization and information and communication technologies (ICTs), such as the Internet and intranets (e.g., Castells, 2000; Porter, 2001). Organizations often rely on acquired knowledge from past experiences to make higher quality decisions on business strategies for better future performance. In this context, Knowledge Management (KM) and Organizational Memory (OM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 75 publications
0
10
0
5
Order By: Relevance
“…After the implementation of the methodology, and the strategy planning process, different stakeholder groups in both cases were interviewed to seek their perceptions about the elements of the methodology. Individual perspectives are known to impact interpretation of facts in organisational contexts [89]. For this reason a qualitative approach was used to capture stakeholders' interpretation of strategy formulation.…”
Section: Resultsmentioning
confidence: 99%
“…After the implementation of the methodology, and the strategy planning process, different stakeholder groups in both cases were interviewed to seek their perceptions about the elements of the methodology. Individual perspectives are known to impact interpretation of facts in organisational contexts [89]. For this reason a qualitative approach was used to capture stakeholders' interpretation of strategy formulation.…”
Section: Resultsmentioning
confidence: 99%
“…Job-related tacit knowledge includes know-who, know-what, know-when, knowwhere, know-how, and know-why. Through a longitudinal study, Hatami, Galliers and Huang [10] confirmed the impacts of OM utilization on effective strategic decisions. Other studies have found that the effective use of OM depends on how well information technology can be called upon to assist in problem solving (ES), decision making (DSS), workflow management (WFMS), and organizational learning [14][15][16][17].…”
Section: Introductionmentioning
confidence: 87%
“…Knowledge assets can be classified into four types: conceptual, experiential, routine, and systematic. Some scholars have adopted the term 'organizational memory' (OM) to highlight the importance of extending, amplifying, and utilizing the knowledge assets of an organization effectively [9][10][11][12]. From a functional viewpoint, OM involves the same processes as those of knowledge management, but with an emphasis on organizational settings and business goals.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, information technology supports the process of retrieving and storing capabilities to initiate organizational memory for future use in the decision-making process (Sandoe & Olfman, 1994). Hence, the relationship between knowledge capturing and organizational memory became a key issue to the effectiveness of organizational performance and strategic decision-making (Hatami et al, 2003). Knowledge capturing as the process collects expertise and knowledge to store it in the organizational memory and use it for continued learning and achieving business innovation (Nonaka & Takeuchi, 1995;Salleh et al, 2013).…”
Section: Knowledge Capturingmentioning
confidence: 99%